Dodd-Frank one year on: Implications for shadow banking - Tobias Adrian (Federal Reserve Bank of New York, 2011)
One year after passage of the Dodd-Frank Act (DFA), regulators proposed several of the rules required for its implementation. In this paper, I discuss some aspects of proposed DFA rules in light of shadow banking. The topics are risk-retention rules for securitized products and the impact of capital reforms on asset-backed commercial paper (ABCP) conduits. While the reform of securitization is resulting primarily from DFA, changes in accounting standards, together with the Basel capital reforms, have had important impacts on the economics of ABCP conduits.
Keywords: G01; G28; 330; shadow banking; regulation